The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21228690
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Amplification and Functional Dependency of the Gamma Actin Gene ACTG1 in Uterine Cancer

Abstract: Sarcomere and cytoskeleton genes, or actomyosin genes, regulate cell biology including mechanical stress, cell motility, and cell division. While actomyosin genes are recurrently dysregulated in cancers, their oncogenic roles have not been examined in a lineage-specific fashion. In this report, we investigated dysregulation of nine sarcomeric and cytoskeletal genes across 20 cancer lineages. We found that uterine cancers harbored the highest frequencies of amplification and overexpression of the gamma actin ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, FCRL4, usually expressed on the memory B cells under infection, it’s overexpression also could impede antigen-induced BCR signaling 43 . Besides, ACTG1 44 and FAM3C 45 46 , which were reported to promote tumor development, were also up-regulated in this cluster. For B-c3, it was defined as follicular B cells for the expression of IGHD and FCER2.…”
Section: Resultsmentioning
confidence: 85%
“…However, FCRL4, usually expressed on the memory B cells under infection, it’s overexpression also could impede antigen-induced BCR signaling 43 . Besides, ACTG1 44 and FAM3C 45 46 , which were reported to promote tumor development, were also up-regulated in this cluster. For B-c3, it was defined as follicular B cells for the expression of IGHD and FCER2.…”
Section: Resultsmentioning
confidence: 85%
“…We established a BLCA prognostic signature based on 7 AS events, in which C19orf57|47943|ES, ACTG1|44120|RI, DYM|45472|ES and HPCAL1|52658|ES were protective AS events, and ANK3|11845|AP, GRIK2|77096|AT and PTGER3|3415|AT were dangerous AS events. ACTG1 is overexpressed in uterine cancer cells, and shows an inhibitory response to immunotherapy [52]. Aerobic glycolysis inhibits the proliferation of hepatocellular carcinoma (HCC) cells by downregulating ACTG1, and a high level of ACTG1 is significantly related to advanced hepatoma [53].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 26 ] Similarly, uterine cancers harbored 5%–20% of ACTG1 gene amplification or overexpression, whose higher expression was correlated with unfavorable prognosis. [ 27 ] Intriguingly, bioinformatic analyses revealed that high expression of ACTG1 may promote colon adenocarcinoma cell growth, but was relative to higher survival rate. [ 28 ] Therefore, detailed and specific roles of ACTG1 in distinct cancer types needs further investigation.…”
Section: Discussionmentioning
confidence: 99%